Development of a heterogeneous phantom to measure range in clinical proton therapy beams. (January 2022) - Cook, H.; Lambert, J.; Thomas, R.; Palmans, H.; Hussein, M.; Clark, C.H.; Royle, G.; Pettingell, J; Lourenço, A
Highlights: New phantom for range verification and audit of clinical proton beams. Radiochromic film accurately measures range shift within heterogeneous phantom. Validation of film ranges via Monte Carlo and scaled depth methods. Phantom tested through treatment workflow to assess audit application. Abstract: Purpose: In particle therapy, determination of range by measurement or calculation can be a significant source of uncertainty. This work investigates the development of a bespoke Range Length Phantom (RaLPh) to allow independent determination of proton range in tissue. This phantom is intended to be used as an audit device. Method: RaLPh was designed to be compact and allows different configurations of tissue substitute slabs, to facilitate measurement of range using radiochromic film. Fourteen RaLPh configurations were tested, using two types of proton fluence optimised water substitutes, two types of bone substitute, and one lung substitute slabs. These were designed to mimic different complex tissue interfaces. Experiments were performed using a 115 MeV mono-energetic scanning proton beam to investigate the proton range for each configuration. Validation of the measured film ranges was performed via Monte Carlo simulations and ionisation chamber measurements. The phantom was then assessed as an audit device, by comparing film measurements with Treatment Planning System (TPS) predicted ranges. Results: Varying the phantom slab configurations allowed for measurable range differences, and the best combinations of heterogeneous material gave agreement between film and Monte Carlo on average within 0.2% and on average within 0.3% of ionisation chamber measurements. Results against the TPS suggest a material density override is currently required to enable the phantom to be an audit device. Conclusion: This study found that a heterogeneous phantom with radiochromic film can provide range verification as part of a dedicated audit for clinical proton therapy beams.